Towards self-consistent plasma modelisation in presence of neoclassical tearing mode and sawteeth: effects on transport coefficients. (7th November 2017) - Basiuk, V; Huynh, P; Merle, A; Nowak, S; Sauter, O
Abstract: The neoclassical tearing modes (NTM) increase the effective heat and particle radial transport inside the plasma, leading to a flattening of the electron and ion temperature and density profiles at a given location depending on the safety factor q rational surface (Hegna and Callen 1997 Phys. Plasmas 4 2940). In burning plasma such as in ITER, this NTM-induced increased transport could reduce significantly the fusion performance and even lead to a disruption. Validating models describing the NTM-induced transport in present experiment is thus important to help quantifying this effect on future devices. In this work, we apply an NTM model to an integrated simulation of current, heat and particle transport on JET discharges using the European transport simulator. In this model, the heat and particle radial transport coefficients are modified by a Gaussian function locally centered at the NTM position and characterized by a full width proportional to the island size through a constant parameter adapted to obtain the best simulations of experimental profiles. In the simulation, the NTM model is turned on at the same time as the mode is triggered in the experiment. The island evolution is itself determined by the modified Rutherford equation, using self-consistent plasma parameters determined by the transport evolution. The achieved simulation reproduces the experimental measurements within the error bars, before and during the NTM. A small discrepancy is observed on the radial location of the island due to a shift of the position of the computed q  = 3/2 surface compared to the experimental one. To explain such small shift (up to about 12% with respect to the position observed from the experimental electron temperature profiles), sensitivity studies of the NTM location as a function of the initialization parameters are presented. First results validate both the transport model and the transport modification calculated by the NTM model.